28. Monitoring in neonatal hypoxic-ischemic encephalopathy undergoing therapeutic hypothermia: Comparison of multi-channel, two-channel and amplitude integrated EEGs. Issue 1 (January 2015) - Toffoli, E.; Scarabel, F.; Agatiello, M.; Suppiej, A.
<x xml:space="preserve">Abstract</x> This study aimed to compare seizure detection by means of multichannel standard EEG with two simplified monitoring methods (amplitude integrated-aEEG and two-channel C3-C4-EEG), in neonatal hypoxic-ischemic encephalopathy (HIE) undergoing therapeutic hypothermia, since in this aetiology of neonatal seizures the issue has not yet been specifically addressed. Blind identification of seizure activity by three independent researchers was done on 100 h of multichannel EEG, C3-C4-channels EEG and aEEG traces obtained from 11 different neonates. 147 seizures were detected by multichannel EEG inspection; 75% of seizures were detected by aEEG, 97% by two- channel EEG. Furthermore, 10 sequences of paroxysmal activity on C3-C4 channels EEG and 12 notches on aEEG were mistakenly classified as seizures. One patient with HIE complicated by stroke had 4 occipital seizures: none was recognized on aEEG, only 1/4 with forward diffusion was recognized by two-channel EEG. In the subgroup of neonatal seizures occurring in HIE undergoing hypothermic treatment two-channel EEG performed better, as seizure detector, than aEEG; both methods showed false positives. Multi-channel EEG had an added value especially in identification of seizures outside the parasagittal sites suggesting occurrence of stroke.